A Review of Gene, Drug and Cell-Based Therapies for Usher Syndrome - French, Lucy S.; Mellough, Carla B.; Chen, Fred K.; Carvalho, Livia S. (Frontiers in Cellular Neuroscience, 2020)
Usher syndrome is a genetic disorder causing neurosensory hearing loss and blindness from retinitis pigmentosa (RP). Adaptive techniques such as braille, digital and optical magnifiers, mobility training, cochlear implants, or other assistive listening devices are indispensable for reducing disability. However, there is currently no treatment to reduce or arrest sensory cell degeneration. There are several classes of treatments for Usher syndrome being investigated. The present article reviews the progress this research has made towards delivering commercial options for patients with Usher syndrome.